Effect of an arm swing on countermovement vertical jump performance in elite volleyball players - Vaverka, F.; Jandacka, D.; Zahradnik, D.; Uchytil, J.; Farana, R.; Supej, M.; Vodicar, J. (Journal of Human Kinetics, 2016)
The aim of this study was to determine how elite volleyball players employed the arm swing (AS) to enhance their jump performance. The study assessed how the AS influenced the duration and magnitude of the vertical ground reaction force (VGRF) during the main phases (preparatory, braking and accelerating) of the countermovement vertical jump (CMVJ), the starting position of the body at the beginning of the accelerating phase and the moment when the AS began contributing to increasing the jump height. Eighteen elite volleyball players performed three CMVJs with and without an AS. Kinetics and kinematics data were collected using two Kistler force plates and the C-motion system. The time and force variables were evaluated based on the VGRF, and the position of the body and the trajectory of the arm movement were determined using kinematic analysis. The AS improved the CMVJ by increasing the jump height by 38% relative to jumping without an AS. The AS significantly shortened the braking phase and prolonged the accelerating phase, however, it did not influence the preparatory phase or the overall jump duration. The AS also significantly increased the average force during the accelerating phase as well as the accelerating impulse. The AS upward began at 76% into the overall jump duration. The AS did not influence the body position at the beginning of the accelerating phase. These findings can be used to improve performance of the CMVJ with the AS and in teaching beginning volleyball players proper jumping technique.